Integrated reporting epiphenomenon: benefits and challenges / Siti Sakinah Azizan - Azizan, Siti Sakinah (Faculty of Accountancy, 2021)
Integrated reporting has been widely discussed in recent years by looking from the views of industrial practices and academicians. We can define integrated reporting as one of corporate reporting that integrates financial and non-financial aspects to enhance the company's value. It covers six domains of social aspects: financial, manufacturing, intellectual, human, social and relationship, and natural capital (IIRF, 2021). The evolution of integrated reporting started in 2013 until the International Integrated Reporting Council (IIRC) had established the International Integrated Reporting Framework (IIRF) (updated in 2021). This framework is a guidance where the Council has already established the guiding principles, content elements, and fundamental concepts inside the integrated report. As a result, the report's information will give value-added to the stakeholders, and of course to the company itself.